2023
DOI: 10.1093/ced/llad325
|View full text |Cite
|
Sign up to set email alerts
|

Lentigo maligna and lentigo maligna melanoma in patients younger than 50 years: a multicentre international clinical–dermoscopic study

Caterina Longo,
Alberto Sticchi,
Alex Curti
et al.

Abstract: Background LM/LMM is usually diagnosed in elderly patients when it is a large lesion. However, it is important to detect it at an earlier stage to minimize the size of the surgical procedure. Objective To determine the clinical, dermoscopic and confocal features of LM/LMM in patients <50 years old Method This study included cases of consecutively excis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The incidence of melanoma arising on chronically sun-damaged skin is difficult to estimate, but evidence suggests that LM and LMM rates are steadily increasing, faster than any other melanoma subtype [2]. Because of the association with cumulative sun damage, LM/LMM is much more common in elderly people; however, a multicentric study conducted by Longo et al showed that LM is not a disease limited to the elderly [4]. LM presenting in young adults tends to be smaller and with fewer dermoscopic criteria, which makes the diagnosis difficult [4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of melanoma arising on chronically sun-damaged skin is difficult to estimate, but evidence suggests that LM and LMM rates are steadily increasing, faster than any other melanoma subtype [2]. Because of the association with cumulative sun damage, LM/LMM is much more common in elderly people; however, a multicentric study conducted by Longo et al showed that LM is not a disease limited to the elderly [4]. LM presenting in young adults tends to be smaller and with fewer dermoscopic criteria, which makes the diagnosis difficult [4].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the association with cumulative sun damage, LM/LMM is much more common in elderly people; however, a multicentric study conducted by Longo et al showed that LM is not a disease limited to the elderly [4]. LM presenting in young adults tends to be smaller and with fewer dermoscopic criteria, which makes the diagnosis difficult [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations